Produção e obtenção de ciclodextrinas produzidas por CGTases bacterianas - Sanches, Raisa Déli de Oliveira [UNESP] (2014)
The cyclomaltodextrin glucanotransferase ( EC 2.4.1.19 ) is an enzyme able to form cyclodextrin from starch . Cyclodextrins are cyclic oligosaccharides , which are the main types α - , β - and γ - CD which have 6, 7 and 8 glucose units connected by α - 1, 4 bonds. Two bacterial alkalophilic Bacillus sp subgroup alcalophilus E16 and Paenibacillus campinasensis H69 -3 was studied due to their good CGTase production, both of which were isolated from soil samples. The enzymatic activity was studied using the methods already pre-determined in previous studies, as dextrinizante, CD-phenolphthalein and protein determination. To achieve the purification and ultrafiltration processes were used for purification gel filtration resin Sephadex G-75. From these processes significant results were obtained for the purified extract produced by Bacillus sp subgroup alcalophilus E16 gave a purification factor of 35.4 times, a yield of 34.1% and a specific activity of 13.10 U / mg , while the purified extract of Paenibacillus campinasensis H69-3 resulted in a purification factor of 94.5 times , a yield of 33.2 % and specific activity of 23.64 U / mg . Tests were made for the production of cyclodextrins using concentrated crude extract by ultrafiltration CGTase produced by Paenibacillus campinasensis H69 3, hydrolysis of starches from different profile than 1.0 % , the enzyme acted converting starch into β- CD best in rice starch and tapioca , whereas a concentration of 2.5 % and better conversion is given cassava and corn starch . As for dextrinizing the starch, the concentrations of 1.0% and 2.5% showed the same profile hydrolysis , and cassava starches , potato and soluble showed better conversion, when compared to starches of rice and corn. Dextrinisation of starch was more effective at 1.0% concentration , because practically all starch was hydrolyzed at a concentration of 2.5% was slower hydrolysis , for 24 hours, the starches in the study were ...